2015
DOI: 10.1016/j.wasman.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A multi-criteria analysis of options for energy recovery from municipal solid waste in India and the UK

Abstract: Energy recovery from municipal solid waste plays a key role in sustainable waste management and energy security. However, there are numerous technologies that vary in suitability for different economic and social climates. This study sets out to develop and apply a multi-criteria decision making methodology that can be used to evaluate the trade-offs between the benefits, opportunities, costs and risks of alternative energy from waste technologies in both developed and developing countries. The technologies co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(67 citation statements)
references
References 46 publications
0
59
0
8
Order By: Relevance
“…In this study, a linear additive model was applied, where a simple MCA matrix was built and WtE technologies were assessed based on four main criteria: environmental, economic, social, and other criteria (Figure 8) (for details on the method, please see Reference [66]). The selection of the assessment criteria and subcriteria was in light of relevant literature [38,70]. The assessment was based on the energy recovery figures calculated using Equations (8)- (11), along with the costs of using WtE technologies and various qualitative criteria, which were taken from published studies [14,16,64,[71][72][73].…”
Section: Assessing Various Wte Technologies In Terms Of Effectivenessmentioning
confidence: 99%
“…In this study, a linear additive model was applied, where a simple MCA matrix was built and WtE technologies were assessed based on four main criteria: environmental, economic, social, and other criteria (Figure 8) (for details on the method, please see Reference [66]). The selection of the assessment criteria and subcriteria was in light of relevant literature [38,70]. The assessment was based on the energy recovery figures calculated using Equations (8)- (11), along with the costs of using WtE technologies and various qualitative criteria, which were taken from published studies [14,16,64,[71][72][73].…”
Section: Assessing Various Wte Technologies In Terms Of Effectivenessmentioning
confidence: 99%
“…According to Greater London Authority (2008), the incineration technology investment cost is in the range 540-740 USD t y -1 (400-550 £ t y -1) : For example, for Case 1 with the lower heating fuel (MSW2), a CAPEX of 7530 USD kW -1 is obtained. Yap and Nixon (2015) estimated that, in the case of England, the investment cost for gasification ranges from 620 to 850 USD t -1 per year: for Case 4, CAPEX varies from 3636 to 8945 USD kW -1 according to the lower heating value considered. Table 3 presents the main economic parameters of each one of the four analysed cases, as well as the selling price of electricity and average electricity cost.…”
Section: Economic Assessmentmentioning
confidence: 99%
“…Unfortunately, nowadays we can observe that statistics confirm a lack of creation due to the inertia in technological transfer regarding restructuration and decentralization on power systems. In their recent publications, many authors [11][12][13][14][15][16] have stated that for solving a problem by BOCR analysis, they consider both positive attributes (benefits and opportunities) and negative ones (costs and risks) to determine a preference of alternatives in relation to a specific goal. They have defined for costs the following constituents: the capital cost (investment), operation and maintenance cost, pretreatment cost, land use cost, and finally ecological damage cost.…”
Section: Bocr Sub-nets Developments For Business Electricity Sustainamentioning
confidence: 99%
“…In a recent publication [13], authors have reviewed the MCDM methods of sustainability and have highlighted their great potential in the field of energy. AHP is the first popular method, and it was found that AHP and its associated family of methods account for 65% of the published papers.…”
Section: An Overview On Ahp-bocr Concept Developmentmentioning
confidence: 99%